Deciding to discontinue prescribed psychotropic medication: A qualitative study of service users' experiences. (7th June 2021) - Watts, Mike; Murphy, Esther; Keogh, Brian; Downes, Carmel; Doyle, Louise; Higgins, Agnes
Abstract: Many mental health service users decide to discontinue their psychotropic medication at some stage in the treatment process; however, few studies have captured these experiences. This study aimed to explore people's experiences of coming off medication. A qualitative descriptive design and individual interviews with 23 people who experienced coming off medication were employed. COREQ checklist was used. Data were analysed using inductive and deductive approaches and six major themes were developed. Findings suggest that while medication was useful for many in the short‐term, the adverse effects had significant impact and contributed to the decision to come off medication. Participants also reported being driven by a questioning of the biomedical model of treatment and the belief that there were other strategies to manage their distress. Mixed experiences of support from healthcare professionals for the medication cessation process were reported. The discontinuation process was often difficult resulting in changes in mood and behaviour which for many culminated in relapse of distress, rehospitalization and return to medication. To support the process of coming off and staying off medication, participants identified a range of useful strategies but particularly highlighted the importance of peer support. Findings from this study demonstrate the importance of mental health nurses having a collaborative discussion with service users which may support safer decision‐making and lessen the risk of people discontinuing medication abruptly. Finding also indicates a need for robust studies that develop and test interventions to support people who wish to discontinue psychotropic medications.